Prispevek k določevanju porekla sladkorja v vinih Republike Slovenije s pomočjo nuklearne magnetne resonance (NMR) : doktorska disertacija - Kocjančič, Mitja (Zagreb : M. Kocjančič, 1995)
Summary: Enrichment of grape must and young wine with sugar in order to rise the natural alcohol content in wine is allowed in all countries of the European Union (EU) only under certain conditions. Slovene "Law on wine and other products from grape and wine" (Official Gazette of the Republic Slovenia, No. 16/74) also forbids the correction of must and grapes by adding sugar, concentrated must, other sugar substances and acids. Exceptionally, the enrichment with sugar or concentrated must is allowed if, due to the consequences of unfavourable weather conditions or diseases felt on vine, less sugar is recorded in grapes, must or grape pulp than the normal quantity allowed for certain grape variety grown in certain vine growing district.
All this refers to the great interest that has been taken in finding a sensitive and reliable analysis which could be used for determination of enrichment of grape must or wine, and which will also affect the future exports of Slovene wines to the EU countries where the imports of enriched wine will be forbidden by a provision. L'Office International de la Vigne et du Vin has recommended to study the required method of determination of sugar origin in wines using nuclear magnetic resonance developed by Prof. G.J. Martin and Prof. S. Brun.The origin of ethanol in wine could be controlled by the ratio between deuterium and hydrogen situated on particular atoms of carbon and oxygen.
It was established that these ratios were different and depended on whether ethanol resulted from natural grape sugar or from beet or cane sugar. From the literature it is evident that it is necessary for each vine growing district to investigate the results prescribed by the method with regard to variety and origin of vine. For this purpose and in frame of our investigations the prescribed method was used in order to process 26 grape samples of major export wine varieties taken in all three vine growing regions in Slovenia. Saccharose added to must before fermentation was proved by means of SNIF-NMR method according to isotopic ratios (D/H)1 and (D/H)2 expressed with regard to standard values of wines that had not been enriched.
From the results it is evident that all the wine samples to which sugar was added before fermentation, regardless of variety, presented higher "R" value.
Sveučilište u Zagrebu, Prehrambeno-biotehnološki fakultet, Zagreb, 1995
Bibliografija: str. 214-220
Summary
Keywords: Vino i vinarstvo -- Slovenija -- Disertacije; Vino i vinarstvo -- Analiza -- Disertacije; Nuklearna magnetska rezonancija -- Disertacije